Older Black Adults' Satisfaction and Anxiety Levels After Completing Alternative Versus Traditional Cognitive Batteries. (27th September 2018) - Gamaldo, Alyssa A; Tan, Shyuan Ching; Sardina, Angie L; Henzi, Carolyn; Guest, Rosalyn; Ross, Lesley A; Willingham, Kurtis; Zonderman, Alan B; Andel, Ross A
Abstract: Objective: The objective of this study was to examine satisfaction, test anxiety, and performance using computer-based cognitive batteries versus a paper-and-pencil neuropsychological battery among older Blacks. Method: Self-identified Black adults ( n = 87, age range: 55–86; mean education = 14) completed two computer-based tests (CogState and Joggle) and a paper-and-pencil neuropsychological battery. After each battery, participants reported their testing anxiety and satisfaction using the batteries. Descriptive, correlational, and regression analyses compared satisfaction, anxiety, and performance across the batteries. Results: Majority of the participants reported more satisfaction with the computer-based (Joggle: 66%; CogState: 77%) than the neuropsychological (52%) battery. Participants also reported less testing anxiety after completing the computer-based batteries than the neuropsychological battery, F (2, 172) = 22.96, p < .001. Older adults' familiarity and comfort level with the computer were not associated with their performance on the computer-based tests ( p > .05). Although testing anxiety was not associated with performance across the batteries, age and education quality were uniquely associated with performance on the CogState and neuropsychological batteries. Conclusions: Computer-based cognitive batteries appear to be less intimidating than the commonly used paper-and-pencil neuropsychological tests for Black adults. Thus, these cognitive batteries may be useful tools for monitoring older Blacks' cognitive status.